2023
DOI: 10.3390/su151914643
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbiome: Diversity, Benefits and Interactions with Plants

Poonam Chauhan,
Neha Sharma,
Ashwani Tapwal
et al.

Abstract: Plant roots aid the growth and functions of several kinds of microorganisms such as plant growth-promoting rhizobacteria, mycorrhizal fungi, endophytic bacteria, actinomycetes, nematodes, protozoans which may impart significant impacts on plant health and growth. Plant soil–microbe interaction is an intricate, continuous, and dynamic process that occurs in a distinct zone known as the rhizosphere. Plants interact with these soil microbes in a variety of ways, including competitive, exploitative, neutral, comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 453 publications
0
6
0
Order By: Relevance
“…The rhizosphere of plants contains diverse microbial communities, such as actinomycetes, bacteria, fungi, and protozoa, which interact with plant roots and each other. Climatic conditions, soil texture, chemistry, and plants' genetic assets may closely influence the formation of these communities and plant-pathogen interactions in the rhizosphere [50,51]. These factors may affect the resistance of plants to pathogens and may also play a role in the transition of Fusarium species, which were found to be weakly parasitic in this study, to the pathogenic form.…”
Section: Discussionmentioning
confidence: 76%
“…The rhizosphere of plants contains diverse microbial communities, such as actinomycetes, bacteria, fungi, and protozoa, which interact with plant roots and each other. Climatic conditions, soil texture, chemistry, and plants' genetic assets may closely influence the formation of these communities and plant-pathogen interactions in the rhizosphere [50,51]. These factors may affect the resistance of plants to pathogens and may also play a role in the transition of Fusarium species, which were found to be weakly parasitic in this study, to the pathogenic form.…”
Section: Discussionmentioning
confidence: 76%
“…The rhizosphere of plants contains diverse microbial communities, such as actinomycetes, bacteria, fungi, and protozoa, which interact with plant roots and each other. Climatic conditions, soil texture, chemistry, and the plant species or cultivars may closely influence the formation of these communities in the rhizosphere [41]. These factors may affect the resistance of plants to pathogens and may also play a role in the transition of Fusarium species, which were found to be opportunistic in this study, to the pathogenic form.…”
Section: Dry Root Weigth 2022 2023mentioning
confidence: 84%
“…We observed that temporal factors exerted a marked influence on the soil bacterial community composition. The observation that diverse soil fungal symbiomes are more resistant to external interventions is confirmed by the fact that fungal compositions showed a higher correspondence due to ripening, indicating that community resilience increases with diversity [ 41 ]. Computational tools allowed us to perform network comparisons of dynamic systems.…”
Section: Discussionmentioning
confidence: 99%